Did the expectations channel work? Evidence from quantitative easing in Japan, 2001-06 - Chikashi Tsuji (Cogent Economics & Finance, 2016)
The Japanese economy experienced a prolonged period of quantitative easing (QE) over the five years from March 2001 to March 2006. The purpose of this paper is to evaluate the direct and exclusive effects of this rather unconventional monetary policy on financial markets, economic activity, and labor markets in Japan empirically by employing exactly the same testing period with the QE period in most of our examinations. Using a range of variables, we first estimate vector error correction models (VECMs) that consider the cointegrating relations between the Japanese monetary base and other variables in our data-set. We also use Markovswitching dynamic regression (MSDR) models, Bayesian vector autoregressive (VAR) models, and causality analyses to test for robustness. Together, all the above analyses consistently provide a number of interesting findings. First, QE lowered shortand medium-term credit spreads and improved Japanese credit market conditions. Second, QE increased stock prices in Japan and improved market expectations. Third, the QE policy recovered labor market conditions and economic productivity in Japan. Finally, additional analyses of fund flows and economic survey data suggest that the primary transmission channel of this period of Japanese QE policy was the expectations channel.
Keywords: 330; Bayesian VAR model; cointegration; expectations channel; Markov-switching dynamic regression model; portfolio substitution channel; quantitative easing monetary policy; signaling effect; vector error correction model